Towards an ethical online payment system through cryptography and next generation communication network - Hassan, Marwa Yousif; Shuriye, Abdi Omar; Salami, Momoh Jimoh Eyiomika; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran (SERSC, 2017)
Abstract The internet brings unprecedented connectivity and communications for both social and commercial settings. There have been many businesses that offer their products and services completely online. Nowadays, even the break and mortar businesses use the internet in a way or another to promote their offerings and to reach people and places they would have never thought of reaching them before the internet era. Conventional online payment systems such as credit and debit cards have enabled such a revolutionary way of doing business. However, conventional financial system has been generating catastrophic disasters to the world. The great depression of 1930s, the World War II, the dot com bubble at the beginning of the new century, and the recent financial crisis that has begun on 2008; to name a few. This will persist if we keep trusting the old ways of finance. This paper investigates the relatively new online payment system termed “Bitcoin” which embraces intentionally or unintentionally the principle of Islamic finance such as saving, compared to the conventional financial system of borrowing, lending and “Riba” (interest).